DIRECT ENHANCEMENT OF PRESYNAPTIC CALCIUM INFLUX IN PRESYNAPTIC FACILITATION AT APLYSIA SENSORIMOTOR SYNAPSES - Leal, Karina (2009)
Regulation of synaptic transmission by modulation of the calcium influx that triggers transmitter release underlies different forms of synaptic plasticity, and thus could contribute to learning. In the mollusk Aplysia, the neuromodulator serotonin (5-HT) increases evoked transmitter release from sensory neurons and thereby contributes to dishabituation and sensitization of defensive reflexes. We combined electrophysiological recording with fluorescence measurements of intracellular calcium in sensory neuron synapses in culture to test whether direct up-modulation by 5-HT of calcium influx triggered by single action potentials contributes to facilitation of transmitter release. We observe increases in a previously undescribed calcium influx that are strongly correlated with increases in the amplitude of the evoked postsynaptic potentials and which cannot be accounted for by action potential prolongation. Our results suggest that direct modulation of a presynaptic calcium conductance that controls neurotransmitter release contributes to the presynaptic facilitation that underlies a simple form of learning.